Peningkatan Proses Pembelajaran Tematik Terpadu Menggunakan Model Problem Based Learning (PBL) Sekolah Dasar - Astugiawa, Peggy; Zaiyasni, Zaiyasni (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2019)
The purpose of this research is to describe the improvement student learning outcomes of integrated thematic learning by using Problem Based learning model at Grade V SDN 11 Aur Kuning Bukittinggi city. Type of the research is classroom action research  by using qualitative and quantitative approach. The subjects of the research were teacher and 30 grade V students. Therefore, the Problem Based Learning model could improve the students learning outcomes of integrated thematic learning. The results of lesson plan observation on cycle I was 84,72%, and cycle II was 94,44%. The observation of teacher on cycle I was 78,56% and cycle II was 92,85%. The observation of student  on cycle I was 85,71% and cycle II was 92,85%. It can be concluded in the study learning using problem based learning modelcan improve the learning process of elementary school.